Strategic (Inconsistent) Disclosures and Sophisticated Investors: Evidence from Hedge Funds - LIU, YICHANG; MADSEN, JOSHUA; ZHOU, FRANK S. (Journal of Accounting Research, 2026)
ABSTRACT Recent SEC regulations require that qualified hedge fund advisers provide their investors with narrative disclosures of their business and operations. We find that 40% of these disclosures omit or de‐emphasize information regarding advisers' operational and investment risks when compared to other sources of public information. Funds with such “inconsistencies” are associated with predictably lower fund performance but do not differ in their fund flows, flow‐performance relation, ownership structure, or management fees. These results are consistent with investors being subject to limited strategic thinking, which prevents them from fully unraveling the implications of strategic omissions. This, in turn, contributes to advisers' successful use of discretion to de‐emphasize information with adverse performance implications. Our findings suggest that information processing frictions can facilitate nondisclosure, even in markets with sophisticated investors.